АСОСИЙ ГИМНАСТИКАДА ҲАРАКАТ ВА КАСБИЙ БИЛИМ ҲАМДА КЎНИКМАЛАРИНИ ШАКЛЛАНТИРИШ - Хайтметов, И.С.; Мусаева, А.Р. (SCIENCE and SOCIETY, 2023)
The main issues considered in the work are the organization of educational and methodological activities of future teachers and trainers on gymnastics, the implementation of didactic principles important for physical education: integrity, optimality, professional and pedagogical orientation of training.